2017
DOI: 10.5455/ajvs.266925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Replacement of Inorganic Zinc by Organic or Nanoparticles Sources on Growth Performance, Immune Response and Intestinal Histopathology of Broiler Chicken

Abstract: Key words:Broiler chickensOrganic zinc -Nano zinc -Growth performance -Immune response -Intestinal health.Two hundred and twenty-five one day-old avian chicks were used to investigate the effect of different dietary supplemental zinc sources and levels on growth performance, blood picture and biochemical parameters, immune response, carcass characteristics and intestinal morphology of broiler chickens. Birds were randomly allocated into 9 groups which fed on the experimental basal diet supplemented with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
12
16
1
Order By: Relevance
“…The absence of significant differences in carcass parameters of the experimental rabbits agrees with the findings of Dokoupilova et al (2007) who noted that added Se did not affect dressing-out percentage of growing rabbits. These results agree with El-Katcha et al (2017) who reported that carcass parts are numerically similar (P≥0.05) by dietary organic or nanozinc supplementation than the control of broiler chicks. In disagreement with the present results, Ebeid et al(2012) reported that feeding male California rabbits on diets supplemented with organic Se (0.15 or 0.30 ppm) led to an improvement in both carcass weight and dressing percentage compared with their control counterparts.…”
Section: Carcass Traitssupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of significant differences in carcass parameters of the experimental rabbits agrees with the findings of Dokoupilova et al (2007) who noted that added Se did not affect dressing-out percentage of growing rabbits. These results agree with El-Katcha et al (2017) who reported that carcass parts are numerically similar (P≥0.05) by dietary organic or nanozinc supplementation than the control of broiler chicks. In disagreement with the present results, Ebeid et al(2012) reported that feeding male California rabbits on diets supplemented with organic Se (0.15 or 0.30 ppm) led to an improvement in both carcass weight and dressing percentage compared with their control counterparts.…”
Section: Carcass Traitssupporting
confidence: 92%
“…Change of triglycerides and total cholesterol levels in blood plasma may be due to the zinc's role in enzyme action which an integral part of several enzymes (metalloenzymes) that are severed in lipid digestion and absorption (Hazim et al, 2011). These finding are similar with El-Katcha et al (2017) who reported that dietary nano-zinc supplementation non significantly reduced blood serum triglycerides while increased HDL than the control of broiler chicks. In addition, Shunyi et al (2016) reported that blood biochemistry of rabbits, including concentrations of cholesterol, HDL and triglyceride were not significantly affected by supplementation of nano-selenium or sodium selenite.…”
Section: Blood Plasma Constituentssupporting
confidence: 91%
See 1 more Smart Citation
“…It is a component of many enzymes (metallo enzymes) involved in lipid digestion and absorption (Al-Darajiet al, 2011). The present results are disagreement with El-Katcha et al (2017), who illustrated that Nano-Zn supplemented the diet of broiler non significantly decreased serum TG while increased HDL than the control. -16.80 -16.80 -11.20 -11.20 -3.20 Hematological parameters are presented in Table (7).…”
Section: Effect Of Experimental Groups On Growth Performance and Feed Efficiencycontrasting
confidence: 99%
“…These results are in the same line with Siddhartha et al (2016) who stated that birds fed diet supplemented with nano-Zn/kg had greater weight gains and better feed conversion ratio than the control. Also, El-Katcha et al (2017) found that final body weight, BWG and FCR, of broiler chicken were improved by nano-zinc supplementation (30,45 and 60 mg/kg) than the control.…”
Section: Discussionmentioning
confidence: 91%